Impacto de la pandemia covid-19 en la salud mental de los profesionales en el área hospitalaria: una revisión bibliográfica - Alban Arias, Dayana Victoria (2025)
It has been observed that during the COVID-19 pandemic, the impact on frontline workers has been greater compared to other healthcare professionals. The objective was to determine the impact of the COVID-19 pandemic on the mental health of professionals working in the hospital area through a bibliographic review. A systematic literature review was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methodology, which allowed for transparent documentation of the justification for the review and the authors' findings. A total of 31 scientific articles were studied, highlighting that there was a high prevalence of mental disorders during the pandemic, such as anxiety, depression, and post- traumatic stress disorder. It is concluded that the COVID-19 pandemic has had a significant and multifaceted impact on the mental health of professionals working in the hospital area. Health professionals, especially those on the front line, have faced high levels of stress, anxiety, depression, and other mental health problems due to extreme workloads, constant uncertainty, and direct exposure to the virus.